2021
DOI: 10.1371/journal.pone.0255225
|View full text |Cite
|
Sign up to set email alerts
|

Australian bus drivers’ modifiable and contextual risk factors for chronic disease: A workplace study

Abstract: Introduction Little is known about workplace health promotion for bus drivers. Bus drivers are at-risk of chronic disease because they are exposed to the risk factor combination of poor nutrition, low levels of physical activity, high levels of sedentary time and are often overweight or obese. The purpose of this paper is to situate the quantitative baseline data collected from bus drivers within qualitative findings about the socio-cultural context of the workplace. Materials and methods Baseline data about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
4
0
1
Order By: Relevance
“…The prolonged driving hour also increases stress levels and constant exposure to a noisy environment. This association is in agreement with the studies conducted in Mojo, Ethiopia, and Australia [ 39 , 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…The prolonged driving hour also increases stress levels and constant exposure to a noisy environment. This association is in agreement with the studies conducted in Mojo, Ethiopia, and Australia [ 39 , 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…This neglects one important factor: the workers. Note, bus drivers (BDs) are considered as one of the most diseased occupational groups worldwide [1][2][3]. This is a problem for public transport sustainability as in the past decade the workforce shortage became a salient concern in many countries [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the bus driver shortage are well-known: a relatively low salary and demanding working conditions [9,11]. Although the latter can vary from country to country and from one company to another, they have been depicted as tedious for many years [3,[12][13][14]. Indeed, bus drivers are exposed to numerous occupational and environmental hazards at their workplace.…”
Section: Introductionmentioning
confidence: 99%
“… 32 Brodie et al. 33 studied 58 bus drivers and showed that they presented poor health behaviors and high sitting times, which can contribute to overweight and obesity, besides major chronic disease risks. In another study, Gilson et al.…”
Section: Sedentary Behavior and Health Outcomesmentioning
confidence: 99%